2021
DOI: 10.1186/s12876-021-01785-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of tumor markers predicts progression and pathological response in patients with locally advanced gastric cancer after neoadjuvant chemotherapy treatment

Abstract: Background The prognostic values of preoperative tumor markers (TMs) remain elusive in patients with locally advanced gastric cancer (LAGC) after neoadjuvant chemotherapy treatment (NACT). This study aimed to assess and establish a novel scoring system incorporating carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9), carbohydrate antigen 72-4 (CA72-4) to enhance prognostic accuracy for progression-free survival (PFS) and pathological response (pCR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Some studies pointed out AC failed to provide superior survival improvement in R0 resected gastric and esophagogastric junction adenocarcinoma under PEC setting ( 13 , 14 ). However, our previous analyses did not completely favor their idea according to which AC is always a risk factor for LAGC patients’ survival in patients with NAC treatment ( 15 , 16 ). Nevertheless, as several retrospective studies advocated the indiscrimination in survival between post-NAC (yp) and neutral stage ( 17 , 18 ), the strategies may be adapted to variation in yp stage in patients with initial LAGC diagnosis.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Some studies pointed out AC failed to provide superior survival improvement in R0 resected gastric and esophagogastric junction adenocarcinoma under PEC setting ( 13 , 14 ). However, our previous analyses did not completely favor their idea according to which AC is always a risk factor for LAGC patients’ survival in patients with NAC treatment ( 15 , 16 ). Nevertheless, as several retrospective studies advocated the indiscrimination in survival between post-NAC (yp) and neutral stage ( 17 , 18 ), the strategies may be adapted to variation in yp stage in patients with initial LAGC diagnosis.…”
Section: Introductionmentioning
confidence: 72%
“…Various reasons can be responsible for this non-significance: (1) TRG only reflects the response to chemotherapy but might be a poor prognosticator for early-stage patents who are not required for intensive drug-based therapy; (2) current TRG classifications do not account for the involvement of lymph nodes, ypN0 with pretreated cN+ diagnosis should be a more direct indication for chemosensitivity; and (3) current cutoff values for TRG criteria may not achieve optimal discriminative ability. Fifth, the aim of our study was to summarize the impact of PEC on survival (to reach the maximum sample volume) so that some decisive factors for survival were not included in the study according to our previous reports ( 15 , 42 ). The c-index should also increase if more factors were input into the tree model.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of NAT efficacy plays a crucial role in deciding postoperative chemotherapy regimens for LAGC patients. However, there is currently no unified standard for evaluating neoadjuvant treatment response and many authors have proposed various methods, including pathological tumor regression assessed by the TRG system, radiological tumor regression according to RECIST version 1.1 and serum tumor marker [ 5 , 6 , 13 ]. A retrospective study conducted by Wang et al found that TRG (P = 0.042, HR = 1.65) was an independent prognostic factor affecting the OS of GC patients, and patients who had a pathological response to NAT had a better prognosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially in China, GC is the third most common cancer and becomes the second leading cause of cancer deaths [ 2 , 3 ]. In addition, GC is often diagnosed at advanced stage in China with poor prognosis [ 4 ]. Surgical resection is the primary curative therapeutic strategy for GC.…”
Section: Introductionmentioning
confidence: 99%